Device use errors among patients with asthma and COPD and the role of training: a real-life study. Issue 5 (4th July 2021) - Papaioannou, Andriana I.; Bartziokas, Konstantinos; Hillas, Georgios; Fouka, Evangelia; Dimakou, Katerina; Kallieri, Maria; Tsikrika, Stamatoula; Papadaki, Georgia; Papathanasiou, Evgenia; Papaporfyriou, Anastasia; Apollonatou, Vasiliki; Verykokou, Galateia; et al.
ABSTRACT: Background and objectives : Administration of inhaled medication for asthma and COPD is often difficult and incorrect device use is associated with unfavorable outcomes. We aimed to evaluate device use errors in asthma and COPD patients and to associate incorrect use with the patient's characteristics and medical history. Methods : Demographics and medical history were recorded. The use of each prescribed device was evaluated according to predefined steps. Results : 607 patients (49.9% male, median age (IQR) 63 (51, 70) years performed 663 demonstrations (56 patients were using 2 different types of devices). 51.4% were treated for asthma and 48.6% for COPD. 79.6% of demonstrations were performed using DPIs. Errors were documented on 41.2% of demonstrations and were associated with the type of device, p < 0.001. Elderly patients were less frequently using their devices correctly compared to younger patients, 50.8% vs 62.2%, respectively, p = 0.007. Correct demonstrations were more among asthmatics compared to COPD patients 63.1% vs 54.5%, p = 0.024. Incorrect use was associated with more acute exacerbations in the preceding year [median(IQR), 1(0, 2) vs 1(0, 1)], for incorrect and correct use, respectively, p < 0.001. Upon demonstration, 15.5% of patients have never been trained (i.e., undergone actual demonstrations and observation while using their device) by anyone. Errors occurred more frequently among patients who reported not to be trained compared to those who were trained, 67.0% vs 14.6%, respectively, p < 0.001. The commonest error was associated with the inspiration maneuver and accounted for the 48.3% of errors in the DPIs and 53.0% of errors in the MDIs. Conclusion : Device use errors are common and associated with unfavorable outcomes. Trained patients were more likely to use the device correctly.